Theoretical-experimental evaluation of the photocatalytic activity of KCa2Ta3−xNbxO10 - Brito, Arnayra S.; Bouquet, Valerie; Demange, Valerie; Cheviré, François; Guilloux-Viry, Maryline; Marinho, Thiago D.; Souza, Juliana K.D.; Lima, Lais C.; Pinheiro, Nayara A.; Santos, Ieda M.G.; Sambrano, Julio R. [UNESP]; Albuquerque, Anderson R.; et al. (Elsevier, 2019)
KCa2Ta3−xNbxO10 samples were synthesized by solid-state reaction and evaluated on the hydroxylation of terephthalic acid under UVC irradiation. Computational simulations via DFT were carried out in order to study their structural and electronic properties. Theoretical results show good agreement with experimental data, regarding lattice parameters and band-gap energy values and indicated that the photocatalytic performance for hydroxyl radicals production is directly related to the degree of octahedral distortions in these materials.
Keywords: DFT; Dion-Jacobson perovskite; Octahedra distortion; Tantaloniobates